LE PATRIMOINE, TRANSMETTRE, SOUMETTRE OU DÉMETTRE ? CE QUE LE DROIT PEUT APPORTER À LA COMPRÉHENSION DE LA PSYCHANALYSE - AMAR, Jacques (Studia Universitatis Babeș-Bolyai Philosophia, 2019)
The purpose of this article is to show that the emergence and development of psychoanalysis cannot be dissociated from the legal framework within which this discipline is embedded. It shows how the links between heritage, person and identity are at the heart of the problems facing our contemporary societies.